Palinoestratigrafia e paleoambientes da formação Solimões, poços 1AS-34-AM e 1AS-31-AM, borda noroeste da Bacia do Solimões - Kachniasz, Karina Eloiza (2016)
Palynological analyses were carried out on 48 samples collected in 1AS-34-AM and 1AS-31- AM wells, from Solimões Formation, northwestern Solimões Basin, Amazonas. A total of 211 morphological set were identified on both wells, of which 123 were reported on well 1AS-34-AM and 181 on well 1AS-31-AM. The data were studied into two lines of study: biostratigraphical and palaeoenvironmental. Regarding the first, the Unitary Association method was applied to compare and complement the results obtained in traditional palynostratigraphy, in order to decrease the effect of discontinuity of the biostratigraphical data, and also, to increase the number of sporomorph markers from this formation’s time deposition. The marker species Ladakhipollenites? caribbiensis, Grimsdalea magnaclavata, Cichoreacidites longispinosus and Echitricolporites mcneillyi were reported on both wells and allow to include these sections into Psilatricolporites caribbiensis and Echitricolporites-Alnipollenites subzones sensu Lorente (1986). These subzones outpoint late Miocene and Pliocene age. The quantitative method produced seven unitary associations and four local zones, which can be identified by 21 species and/or pars of species characteristic. Additionally, UA’s contributed giving biostratigraphical meaning to species recently described on literature. Comparisons between two methods indicate that both wells are contemporaneous, with similar species composition between them. Regarding the second line of study, a general palaeoenvironmental framework was determinate to intervals from this formation, by means of taxonomical affinities described on literature. A record of foraminiferal organic lining on well 1AS-31-AM corroborates hypotheses of marine incursions into amazon basin during the Neogene. Also, suggests an age younger than literature proposes to these episodes, with 5,3 millions of years old, during the Pliocene.